(untitled) (Nordic Journal of African Studies, 2000)
The paper is a semantic, phonological, morphological and socio-linguistic analysis of 213 French loan-words in the Fula dialect of Masina, Mali, the complete list of French loan-words found in the issues of the monthly newspaper Kabaaru published in the period 1995-1997. The words are classified according to their semantic domains ; most loan-words are found in the domains of technology. It is shown how the loan-words are phonologically and morphologically integrated to different degrees into the linguistic system of Fula. Phonological integration implies a substitution of non-Fula phonemes and an adaptation to Fula syllable structure. Morphological integration, on the other hand, implies the introduction of noun class suffixes. The author has carried out an inquiry to test to what degree a group of newly literate native speakers of Fula living in villages in Masina understand a selection of these French loan-words. The degree of understanding varies significantly between ‘current loan-words’ and ‘learned loan-words’ – the latter group being loan-words that according to the author’s evaluation are not much used outside the pages of Kabaaru. The paper ends with a discussion of the pros and cons of French loan-words in Fula.